A Review of fine grained access control techniques - Shirsath, Rakesh; K. V. Daya Sagar, Dr (International Journal of Engineering and Technology, 2018)
Nowadays cloud computing is most demanding technology where computing resources are availed as per demand through Internet. Cloud computing model also brings many challenges for confidentiality, integrity, privacy of data and data access control. As cloud computing develops vigorously, an increasing number of enterprises and individuals are motivated to upload their data sources to the public cloud server for sharing. It is not entirely credible for enterprises and individuals to transfer data owing to the openness of the cloud server, so they must encrypt data before uploading and also loose direct control of data. Therefore, an elastic access control or fine-grained access control approach for data is urgently required and becomes a challenging open problem. In this paper, the issue of access control is discussed by defining traditional access policies. Attribute based access policy is analysed with its types. Finally, comparison is made among all policies with respect to various parameters.